2015
DOI: 10.1371/journal.pone.0143119
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Various Anthropometric Indices as Risk Factors for Hearing Impairment in Asian Women

Abstract: BackgroundThe objective of the present study was to examine the associations between various anthropometric measures and metabolic syndrome and hearing impairment in Asian women.MethodsWe identified 11,755 women who underwent voluntary routine health checkups at Yeungnam University Hospital between June 2008 and April 2014. Among these patients, 2,485 participants were <40 years old, and 1,072 participants lacked information regarding their laboratory findings or hearing and were therefore excluded. In total 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Moreover, abdominal lipid-related factors were reported to be associated with hearing loss at specific frequency bands [ 25 ]. Abdominal adipose tissue has also been associated with hearing loss in women, [ 8 ] and weight-hip ratio (WHR) may be an indicator of the risk of hearing loss [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, abdominal lipid-related factors were reported to be associated with hearing loss at specific frequency bands [ 25 ]. Abdominal adipose tissue has also been associated with hearing loss in women, [ 8 ] and weight-hip ratio (WHR) may be an indicator of the risk of hearing loss [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies also observed relationships between obesity-related anthropometric indices and hearing loss. For example, one study found that WHR may be a surrogate marker for predicting the risk of hearing loss, [ 18 ] whereas another study suggested that FRAs were associated with hearing loss at specific frequencies, as determined by sex and the presence of diabetes, and that visceral adipose tissue (VAT) is particularly important role for hearing [ 25 ]. Two studies found relationships between BMI and hearing loss, with one finding that underweight and severe obesity were associated with an increased prevalence of hearing loss in a Korean population, and the other reporting that overweight was associated with an increased risk of hearing loss in a Japanese population [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of our research are in accordance with a study that showed significant differences in terms of body height and body mass between male and female students (21). Another indicator which was not taken into account in the study is waist circumference which can be a useful indicator of nutritional status in children and in adults (22), so studying WHR in future studies is highly recommended. Based on a study, people with the highest waist circumference had the greatest tendency for hypertension, diabetes, increased blood fat and metabolic syndrome, compared to those with a normal waist circumference (22)).…”
Section: Discussionmentioning
confidence: 99%
“…Another indicator which was not taken into account in the study is waist circumference which can be a useful indicator of nutritional status in children and in adults (22), so studying WHR in future studies is highly recommended. Based on a study, people with the highest waist circumference had the greatest tendency for hypertension, diabetes, increased blood fat and metabolic syndrome, compared to those with a normal waist circumference (22)). It is known that heredity plays an important and key role in the growth and development in humans.…”
Section: Discussionmentioning
confidence: 99%